2007
DOI: 10.1086/513873
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Tumor Necrosis Factor–α Treatment ActivatesBorrelia burgdorferiSpirochetes 4 Weeks after Ceftriaxone Treatment in C3H/He Mice

Abstract: This report shows that, after ceftriaxone treatment for 5 days, a portion of B. burgdorferi-infected mice still have live spirochetes in their body, which are activated by anti-TNF-alpha treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 49 publications
5
39
0
Order By: Relevance
“…The significance of these findings is, at present, unclear. A recent study reported that B. burgdorferi was found by culture in a few mice treated with anti-TNF antibody either simultaneously or 4 weeks after ceftriaxone therapy [67]. However, the number of mice treated in this study was small and the findings need further verification.…”
Section: The Possible Causes Of Post-lyme Disease Symptomsmentioning
confidence: 65%
“…The significance of these findings is, at present, unclear. A recent study reported that B. burgdorferi was found by culture in a few mice treated with anti-TNF antibody either simultaneously or 4 weeks after ceftriaxone therapy [67]. However, the number of mice treated in this study was small and the findings need further verification.…”
Section: The Possible Causes Of Post-lyme Disease Symptomsmentioning
confidence: 65%
“…Through use of Myd88 -/-mice and intravital microscopy, we have shown that ceftriaxone rapidly (within 24 hours) reduces pathogen burden in the skin, a preferential site of B. burgdorferi infection, and that both ceftriaxone and doxycycline eliminate infectious spirochetes as assessed by real- Previous studies examining antibiotic efficacy in murine Lyme borreliosis used the BbN40 strain (12)(13)(14). Here, we found that antibiotics were effective against 2 strains of B. burgdorferi (BbN40 and Bb914) that represent genotypes that differ in their capacity for dissemination and pathogenicity (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory and others have used the C3H mouse model of Lyme borreliosis to evaluate whether viable B. burgdorferi can persist after antibiotic treatment (12)(13)(14). Using xenodiagnosis with ticks, we showed that spirochetes could be detected for up to 3 months after treatment with either ceftriaxone or doxycycline for B. burgdorferi infection introduced by tick bite (14).…”
Section: Introductionmentioning
confidence: 92%
“…These antibiotic-resistant arthritis patients are usually administered anti-inflammatory drugs following antimicrobial therapy to resolve the arthritis (136). However, a recent study demonstrates that B. burgdorferi DNA may be detected in infected mice treated with a combination of ceftriaxone and antibodies to the inflammatory cytokine TNF-␣, while treatment with ceftriaxone alone yielded no observation of borrelial DNA (157). The authors claim that their findings support the hypothesis of borrelial persistence despite antibiotic treatment.…”
Section: Arthritis Development In the Absence Of B Burgdorferimentioning
confidence: 91%